2018
DOI: 10.1016/j.psyneuen.2018.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Marital distress, depression, and a leaky gut: Translocation of bacterial endotoxin as a pathway to inflammation

Abstract: These bacterial LPS translocation data illustrate how a distressed marriage and a mood disorder history can promote a proinflammatory milieu through increased gut permeability, thus fueling inflammation-related disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(71 citation statements)
references
References 63 publications
1
68
1
1
Order By: Relevance
“…Chronic, elevated inflammation can predispose individuals to developing an inflammation-related disorder like depression. In a study by Kiecolt-Glaser et al married couples were evaluated for increases in inflammation markers such as LPS-binding protein (LBP), soluble CD14 (sCD14), and CRP to determine if increased gut permeability is a potential mechanism for marital distress and depression [45]. LBP and CD14 are typically released in response to bacterial translocation of endotoxins and are markers for leaky gut.…”
Section: Marital Distress Depression and Leaky Gutmentioning
confidence: 99%
“…Chronic, elevated inflammation can predispose individuals to developing an inflammation-related disorder like depression. In a study by Kiecolt-Glaser et al married couples were evaluated for increases in inflammation markers such as LPS-binding protein (LBP), soluble CD14 (sCD14), and CRP to determine if increased gut permeability is a potential mechanism for marital distress and depression [45]. LBP and CD14 are typically released in response to bacterial translocation of endotoxins and are markers for leaky gut.…”
Section: Marital Distress Depression and Leaky Gutmentioning
confidence: 99%
“…We have published a meta-analysis suggesting that patients with irritable bowel syndrome were at higher risk of major depression [37], confirming the potential causal or bilateral relationship between microbiota disturbances and major depression. Several studies have shown microbiota disturbances in patients with major depression; these disturbances are summarized in Table 1 [38][39][40][41][42][43][44][45][46][47][48][49][50]. Probiotics yielded small but significant effects for depression (d = −0.24, p < 0.01) and anxiety (d = −0.10, p = 0.03).…”
Section: Microbiota-orientated Therapies and Their Interest For Majormentioning
confidence: 99%
“…Depression is correlated with an increase in markers of bacterial translocation, gut permeability, and toll-like receptor activation, all important measures of increased immune activity in the gut (Kéri et al, 2014). Additionally, cytokines shown to increase with changes in the microbiome and gut permeability are known to be elevated in depressed patients (Kéri et al, 2014;Schirmer et al, 2016;Kiecolt-Glaser et al, 2018). These cytokines can sensitize the cortisol response pathway, influence the kynurenine pathway, or act directly on neurons and/or glial cells within the brain to propagate depression symptoms (Dantzer et al, 2008;Fritz et al, 2016;Hoshino et al, 2017;Gheorghe et al, 2019).…”
Section: Mucins and The Immune Systemmentioning
confidence: 99%